Two-Sided Markets with Negative Externalities - Markus Reisinger (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2004)
This paper analyses a two-sided market in which two platforms compete against each other. One side, the advertisers, exerts a negative externality on the ther side, the users. It is shown that if platforms can charge advertisers only, a higher degree of competition for users can lead to higher profits because competition on the advertisers' side is reduced. If platforms can charge users as well, profits might increase or decrease, the latter because of increased competition through the additional instrument of the user fee. Nevertheless the equilibrium with user fee is more efficient.
urn:nbn:de:bvb:19-epub-478-5
Keywords: D43; D62; L13; 330; Negative Externalities; Price Competition; Two-Sided Markets